EXCEPTIONAL RATIO ON DEPOSITS IN A SHARIAH ECONOMIC PERSPECTIVE: A STUDY IN BANK MUAMALAT INDONESIA - K, Amiruddin (Yayasan Education and Social Center, 2023)
This study aims to (1) find out the particular ratio calculation for Muamalat Bank Deposits, in this case, the Super Blessing Mudharabah Deposit, and (2) To find out a review of the sharia economic perspective regarding the particular ratio calculation. This research uses a qualitative approach. Data was collected through observation and interview techniques. The results showed that profit sharing depends on the magnitude of HI-1000 each month, so the magnitude of the revenue share continues to change every month. It is different from conventional banks, where profit sharing is very dependent on the interest rate agreed at the beginning. On the other hand, the distribution of an exceptional ratio is only given to deposit customers with a nominal value above IDR 100,000,000. If the nominal is under IDR 100,000,000, the customer will only get the counter ratio according to what the bank determines